Frailty in geriatric head and neck cancer: A contemporary review. (17th October 2018) - Noor, Anthony; Gibb, Catherine; Boase, Sam; Hodge, John‐Charles; Krishnan, Suren; Foreman, Andrew
Abstract : Objective: To provide a summary of the current frailty literature relating to head and neck cancer. Data Sources: Ovid MEDLINE, PubMed, Google Scholar. Methods: A comprehensive review of the literature was performed from 2000 to 2017 using key words frailty, elderly, geriatric, surgery, otolaryngology, head and neck cancer. Results: The aging population has led to an increased diagnosis of head and neck cancer in elderly patients. The prevalence of comorbidities, disabilities, geriatric syndromes and social issues can make treatment planning and management in this population challenging. Chronological age alone may not be the optimal approach to guiding treatment decisions, as there is marked heterogeneity amongst this age group. Individualization of treatment can be achieved by assessing for the presence of frailty, which has growing evidence as an important marker of health status in geriatric oncology. Frailty is a complex geriatric syndrome characterized by a state of increased vulnerability to stressors and is associated with morbidity, mortality, and treatment toxicity. Screening for frailty may provide an efficient method to identify those who would benefit from further assessment or pretreatment optimization, and to provide prognostic information to assist clinicians and patients in formulating the most ideal treatment plan for the elderly individual with head and neck cancer. Conclusions: Frailty has emerged as an important concept in geriatric oncology, with wide significance in head and neck cancer. Incorporating frailty assessments into clinical practice may provide otolaryngologists pertinent information regarding health status and outcomes leading to optimal care of the elderly cancer patient. Laryngoscope, 128:E416–E424, 2018